Peran Forum Kerukunan Antar Umat Beragama (FKUB) Dalam Upaya Penanggulangan Timbulnya Konflik Sosial Keagamaan Di Kota Kediri Tahun 2020 - Achmad Munif; Ropingi el Ishaq (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2021)
The population of Kediri, especially the City of Kediri, is Muslim. Meanwhile, Christians, Catholics, Hindus, Buddhists, Confucians, and Adherents of faith developed quite significantly. This can be seen from the number of adherents, places of worship, and their activity in interfaith organizations. Therefore, to anticipate the spread of SARA issues and the threat of national disintegration, the government then formed FKUB (Forum for Religious Harmony). FKUB Kediri City was formed since 2000 which consists of 6 elements of religion, namely; Islam, Hinduism, Catholicism, Christianity, Buddhism, Confucianism. This study aims to: (1) determine the role of the Inter-religious Harmony Forum (FKUB) in the City of Kediri; and (2) knowing the role of the Inter-Religious Harmony Forum (FKUB) in efforts to overcome the emergence of socio-religious conflicts in Kediri City. Based on the calculation of the sampling technique, the number of research samples was 150 respondents. Data analysis techniques include descriptive and quantitative with simple linear regression analysis. The results showed that the average score of respondents' answers ranged from a score of 4, meaning that the equality of religious communities in Kediri City has been well established; the average score of respondents' answers ranged from a score of 3, meaning that the cooperation of religious communities in the city of Kediri has been established quite well; the average score of respondents' answers ranged from a score of 4, meaning that the policies made by the FKUB in the City of Kediri have been running well; the average score of respondents' answers ranged from a score of 2, meaning that there was no conflict between religious communities in the city of Kediri.